Zur Ausbildung zentralörtlicher Systeme beim Übergang von der semiautarken zur arbeitsteiligen Gesellschaft: Ein Vergleich historischer Abfolgen in Mitteleuropa mit heutigen Verhältnissen in Entwicklungsländern, insbesondere am Beispiel Mexicos - Gormsen, Erdmann (ERDKUNDE, 1971)
Recent investigations in SW Germany have shown that the Christaller model, with its highly evolved hierarchy of central places, has only developed since the beginning of the Industrial Revolution, from a simpler system of a tightly-meshed market network with only a few larger towns. The temporal development stadia which unfolded over a 150 year period can be observed developing in a similar fashion in spatial proximity to each other in developing countries. The Puebla-Tlaxcala in Mexico can be taken as an example. It has the hardly altered market network of the semi-autarchic economic organisation of the Indios in the north, the already clearly visible changes consequent on improved transport development in the south, while in the industrialised central area the traditional market network is being overlain by a system of central places on the classical scale. In this way, a relationship can be demonstrated between the major groupings of the population and the central places of the various levels. Similar observations have been reported from the Near East and other parts of the world. In terms of research methodology, Christaller's telephone method proved most useful as a preliminary technique since Mexico is in the situation of early telephone development. Other methods must naturally be used for more precise definition.